Associations of atrophic gastritis and proton-pump inhibitor drug use with vitamin B-12 status, and the impact of fortified foods, in older adults. Issue 4 (16th June 2021) - Porter, Kirsty M; Hoey, Leane; Hughes, Catherine F; Ward, Mary; Clements, Michelle; Strain, Jj; Cunningham, Conal; Casey, Miriam C; Tracey, Fergal; O'Kane, Maurice; Pentieva, Kristina; McAnena, Liadhan; et al.
ABSTRACT: Background: Atrophic gastritis (AG) and use of proton pump inhibitors (PPIs) result in gastric acid suppression that can impair the absorption of vitamin B-12 from foods. The crystalline vitamin B-12 form, found in fortified foods, does not require gastric acid for its absorption and could thus be beneficial for older adults with hypochlorhydria, but evidence is lacking. Objectives: To investigate associations of AG and PPI use with vitamin B-12 status, and the potential protective role of fortified foods, in older adults. Methods: Eligible participants ( n = 3299) not using vitamin B-12 supplements were drawn from the Trinity-Ulster and Department of Agriculture cohort, a study of noninstitutionalized adults aged ≥60 y and recruited in 2008–2012. Vitamin B-12 status was measured using 4 biomarkers, and vitamin B-12 deficiency was defined as a combined indicator value < −0.5. A pepsinogen I:II ratio <3 was considered indicative of AG. Results: AG was identified in 15% of participants and associated with significantly lower serum total vitamin B-12 ( P  < 0.001) and plasma holotranscobalamin (holoTC; P  < 0.001), and higher prevalence of vitamin B-12 deficiency (38%), compared with PPI users (21%) and controls (without AG and nonusers of PPIs; 15%; P  < 0.001). PPI drugs were used (≥6 mo) by 37% of participants and were associated with lower holoTC concentrations, but only in participants taking higher doses (≥30 mg/d). Regular, compared with nonregular, consumption of fortified foods (i.e., ≥5 and 0–4 portions/wk, respectively) was associated with higher vitamin B-12 biomarkers in all participants, but inadequate to restore normal vitamin B-12 status in those with AG. Conclusions: Older adults who have AG and/or use higher doses of PPIs are more likely to have indicators of vitamin B-12 deficiency. Fortified foods, if consumed regularly, were associated with enhanced vitamin B-12 status, but higher levels of added vitamin B-12 than currently provided could be warranted to optimize status in people with AG.